Using Projects-Based Learning in Improving Students' Critical Thinking Skills to Recycle Waste Cooking Oil - Indah Ningtyas Andalas Putri; Noor Fadiawati; M. Mahfudz Fauzi Syamsuri (Universitas Islam Indonesia, 2019)
This study aims to describe the effectiveness of project-based learning in improving students' critical thinking skills. The research design used was the matching only pretest and posttest control group. The population in this study were all students of class XI MIPA, one of the high schools in Bandarlampung. The research sample was students of class XI MIPA 6 and XI MIPA 4. The data analysis technique used is the non parametric statistical test using U Man Whitney. The results of the study showed that the average posttest of critical thinking skills in the experimental class was greater than in the control class. the average n-gain in the experimental class is medium and low in the control class, indicating that project-based learning is effective in improving students' critical thinking skills. Keywords: critical thinking skills, waste cooking oil, project-based learning